Extensive genetic variability of simian immunodeficiency virus from African green monkeys. - Li, Y (1989)
Serological surveys have revealed that 30 to 50% of wild-caught African green monkeys have antibodies reactive to simian immunodeficiency virus (SIV), a retrovirus related to human immunodeficiency virus (HIV). Although the nucleotide sequence of one SIVagm isolate, Tyo1, was recently reported, the extent of genetic variability among SIVagm isolates remains to be determined. Restriction endonuclease mapping of infectious molecular clones of two SIVagm isolates (266 and 385), described in this note, revealed conservation of only 4 of 39 sites across the genome. Partial sequence analysis of the molecular clones revealed only 80% amino acid sequence conservation in the pol gene. Although the three Kenyan SIVagm isolates, Tyo1, 385, and 266, are more closely related to each other than to other primate lentiviruses, genetic variation among these three isolates is much greater than that observed previously among individual HIV type 1 (HIV-1), HIV-2, or SIVmac isolates. Less variability among HIV-1 and HIV-2 isolates could be explained by recent entry into the human population. The extensive genetic variation in these Kenyan SIVagm isolates should prompt continued examination of SIVagm variability from dispersed geographic regions; SIVagm strains much more closely related to HIV-1, HIV-2, or SIVmac which would be reasonable candidates for recent cross-species transmission may be found.